(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Cardiovascular diseases are the leading causes of death in people of different age categories. The cause of many cardiovascular diseases is atherosclerosis - a chronic disease of the arteries of the elastic and muscular type, accompanied by the deposition of cholesterol and lipoproteins in the intima of the vessels and the occlusion of the lumen of the vessel. With a pronounced narrowing of the lumen of the coronary arteries by an atherosclerotic plaque, coronary heart disease (CHD) can occur. Currently, despite the use of a complex of drugs for the treatment of CHD, mortality from this disease remains significant. In view of this, scientists pay much attention to the study of the complex processes of the occurrence and progression of atherosclerosis, along with other processes leading to atherothrombosis, such as accelerated platelet aggregation. With the development of new methods of laboratory diagnostics, it became possible to study the composition of the intestinal microbiome and its metabolic activity in various diseases.